"Quem sou eu?": Literatura e construção de identidade em alunos do meio rural - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
There are many functions of literature. Among them, that of broadening our horizons, mitigating our fears, putting us in communication with others and even making us recognize who we are. Literature is not disassociated from the subject, from their experiences, their stories, from the desire of those who read, since literature brings with it a set of knowledge that transcends time, which enables us to anticipate future knowledge and explore the universe human, making us free, responsible, critical, with the capacity to modify, autonomously, the space we occupy. In addition, literature has the ability to form sensitive and intelligent personalities, open to new knowledge. Finally, it has important and significant effects on the construction and reconstruction of the identity and reality of the human being. Given this context, this research sought to understand how literature can contribute to the construction of identity in students from rural areas, in order to raise awareness about themselves in students. It is a research with a qualitative approach, which opted for the action-research methodology, in which all those involved actively participate in the research and which has Cultural Pedagogy as its methodological theoretical basis, whose central idea is of a pedagogized society, where teaching transcends the classrooms, as well as the teaching of literature.In this way, we aim to understand how Literature can contribute to the construction of identities in rural students, with the following specific objectives: a) to understand how literature can awaken students' self-awareness; b) verify how the identity of rural students is constructed; c) investigate how empathy with the characters of literary texts contributes to the student's self-knowledge. For the theoretical foundation, we used authors with literature in the classroom, we had as references Cândido (1985, 1995,2011), Dalvi and Jouve (2013) and Cosson (2016,202); in the area of Education, the authors of Cultural Pedagogy: Giroux (1999, 2001, 2005), Martins and Tourinho (2011, 2014) and others such as Candau (2011) and more that emerged throughout the research. In order to analyze the contents, didactic sequences were applied, with different textual genres, in Portuguese language classes. As a category of analysis, we chose 1) identity 2) identification with the characters 3) identity vocabulary. The research took place in a rural school, in the city of Jaraguá, in the north of the State of Goiás. We chose to apply the activities in the 8th and 9th years, of the Final Years of Elementary School II. We hope that this Dissertation can contribute to the understanding of the importance of literature in everyday human life, becoming not only a source of pleasure and fun, but also an inexhaustible means of knowledge.
"Who am I?" : literature and identity building in students from the rural environment
Keywords: Alunos do meio rural - Identidade; Alunos do meio rural - Literatura; Alunos do meio rural - Pedagogia cultural; Students from the Rural Area - Identity; Students from the Rural Area - Literature; Students from the Rural Area - Cultural pedagogy; CIENCIAS HUMANAS::EDUCACAO